2017
DOI: 10.1037/sgd0000215
|View full text |Cite
|
Sign up to set email alerts
|

Male-partnered sexual minority women: Sexual identity disclosure to health care providers during the perinatal period.

Abstract: Male-partnered sexual minority women (SMW) have received little research attention, despite the fact that they represent a large proportion of SMW – particularly child-bearing SMW. Male-partnered SMW are less “out” than female-partnered SMW and will likely be “read” as heterosexual by perinatal providers. Given this, and evidence that pregnant women have unique mental health care needs, the current study focuses on male-partnered SMW (n = 28) during the perinatal period, recruited from Toronto, Canada and Mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…We utilized these broad criteria inclusive of both same-sex behavior and sexual minority identity for feasibility reasons (due to low numbers of LGBQ-identified women presenting for prenatal care during the recruitment period), as well as to include women with same-sex attractions whose partner gender and parental status foreclosed sexual minority identification (as in Budnick, 2016). (See Goldberg, Ross, Manley, & Mohr, 2017, for a comprehensive description of recruitment procedures. )…”
Section: Methodsmentioning
confidence: 99%
“…We utilized these broad criteria inclusive of both same-sex behavior and sexual minority identity for feasibility reasons (due to low numbers of LGBQ-identified women presenting for prenatal care during the recruitment period), as well as to include women with same-sex attractions whose partner gender and parental status foreclosed sexual minority identification (as in Budnick, 2016). (See Goldberg, Ross, Manley, & Mohr, 2017, for a comprehensive description of recruitment procedures. )…”
Section: Methodsmentioning
confidence: 99%
“…Although previous work has shown that lesbian and gay individuals have lower desires to become parents as compared to their heterosexual counterparts (Riskind & Patterson, 2010), for bisexual women, research suggests context-dependent experiences such as partner sex (i.e., bisexual women who are partnered with women have similar desires and intentions as lesbian women; Riskind & Tornello, 2017; Ross, Siegel, Dobinson, Epstein, & Steele, 2012). In addition, research has extensively covered lesbian and gay parenting (Biblarz & Stacey, 2010; Patterson, 2017), but less research has included bisexual individuals (Goldberg, Ross, Manley, & Mohr, 2017; Power et al, 2012; Ross & Dobinson, 2013).…”
mentioning
confidence: 99%
“…There is a growing body of evidence in relation to lesbian women's experiences of reproductive and maternity care, but research addressing the birth experiences and psychological health of lesbian mothers has been limited, and has focused on postnatal depression. Researched even less has been the experiences and psychological health of bisexual women who have male partners at the time of their pregnancy (Goldberg, Ross, Manley, & Mohr, 2017). In addition, research has not captured the complexity of family forms; for example, that with a lesbian couple, the children may be biologically connected to a non-birth parent, or that both partners may be (or may attempt to be) birth parents within that family.…”
Section: Editorialmentioning
confidence: 99%